Analisis Pengaruh Variasi Arus dan Sudut Kampuh dengan Metode Pengelasan GTAW terhadap Sifat Mekanik dan Struktur Mikro Baja ST 41 - Ridhwan Haliq; Himawan Tri Raharjo (LPPM ITK, 2018)
The objective of research is to determine the effect of welding current on the hardness, tensile strength, and microstructure from GTAW welding with ER70S2. This research used ST 41 low alloy steel material containing C = 0,16 %, Si = 0,23 %, Mn = 0,69 %, S = 0,031 %, P=0,019 %, yield point 40 kg/mm2, tensile strength 52 kg/mm2, dan elongation 32 %. ST 41 steel welding is carried out with current variations of 90 A, 110 A and 130 A with GTAW welding methode. Types of variation of the notch use are ][, V and X. The specimens was subjected to hardness, tensile strength, and metallography. Based on the result of hardness test with the factor elimination method in obtaining the angle ][ notch with current 90 A, V notch with current 90 A, and X notch with current 110 A. Tensile test results of the three materials, the highest tensile strength at the X notch with current 110 A is 416,8 N/mm2. The lowest tensile strength is obtained at welds with ][ notch is 360.73 N/mm2. From result of metallograph that we get if X notch with current 110 A is more stable, than ][ notch with current 90 A and V notch with current 90 A.